KECEPATAN TINGKAT PENERIMAAN DAN PERILAKU KONSUMEN TERHADAP PRODUK LAMA YANG MENGALAMI PERUBAHAN DAN PRODUK INOVASI BARU DALAM UPAYA MEMASUKI DAN MEREBUT PASAR - Leli Deswindi (Universitas Bunda Mulia, 2007)
AbstractEffectivities of the promotions have always become a hot issue in marketing field. Several marketers don’t measures the effectiveness of the campaign result. Experiences proved for the decreased of using some traditional method in the campaign activity such as commercial advertisement in electronic media. Marketers prefer to choose the application of other promotion methods. Integrated Media Communication (IMC) is the application of the total campaign tools as an integrated method that has been chosen nowadays. The goal of the IMC is to strengthen the company position in every part of the Product Life Cycle (PLC). Begin with the product development, introduction, growth, maturity and decline. How to understand the period of the acceptance from customers in term of a new product development or a product improvement. The effort of the marketer to build the relations with the customer is the key to maintains the market share, increased the growth of a company and returns the scale of profitability.KeywordsManajemen pemasaran, perilaku konsumen, promosi